Size and morphology controlled synthesis of barium sulfate - Akyol, Emel; Cedimagar, Murat Alper (WILEY-V C H VERLAG GMBH, 2016)
In this work submicron barium sulfate (BaSO4) particles were synthesized successfully by chemical precipitation technique. We focused on the effects of pH and additives on the size and morphology of BaSO4 crystals. Polyacrylic acid, polyvinyl sulfonic acid and ethylenediaminetetraacetic acid were used as crystal growth modifiers. BaSO4 crystals were characterized using scanning electron microscopy, X-ray diffraction, and Fourier transform infrared resonance techniques. The results show that the submicron BaSO4 particles have been synthesized successfully and the particle size of the barium sulfate was effectively controlled under the experimental conditions. Experimental studies revealed that the additive concentration and pH had great effect on the morphology and size of barium sulfate.
Keywords: submicron barium sulfate; chemical precipitation technique; crystal growth modifiers; morphology; BASO4 NANOPARTICLES; CRYSTAL-GROWTH; PRECIPITATION; CRYSTALLIZATION; MICROEMULSION; DIHYDRATE; PARTICLES; Crystallography